Effects of Globalization on National Healthcare Delivery System: The Nigerian Experience (Global Journal of Human-Social Science, 2015)
This paper has three related objectives. First is to chronicle the diverse dimensions to the conceptualization of the subject of globalization. The second is to put forward the argument that globalization as a contemporary social phenomenon has the characteristics and indeed constitutes an important social determinant of health. On this premise, this paper submits that as a social determinant of health, globalization has crucial effects on health status of individuals, small groups or communities, and nation states. The third objective is to briefly account for the exact effects of globalization on Nigeria's health system. Anchored on modernization theoretical platform, this paper canvassed for a level playing field where developing countries are not subservient to their developed counterparts as globalization runs its course. Accordingly, there should be a fair balance in traffic of persons, goods, information and services between the West and less developed third world nations like Nigeria. This measure if adopted will evenly distribute the positive and negative effects of globalization across rich western nations and their poor third world counterparts. With particular reference to Nigeria's health sector, the paper identified brain drain, easy spread of diseases and influx of health risks in forms of cigarettes, junk foods, and toxic wastes as some negative effects of globalization on health.
Keywords: globalization; health; health systems; social determinants of health; westernization